Ayat-Ayat Al-Qur’an Tentang Manajemen Mutu Pendidikan Islam - Sukirno Sukirno; Ahmad Fauzi; Suwelda Suwelda (Journal of Creative Student Research, 2024)
The purpose of writing this article is to find out the verses of the Qur'an about the quality management of Islamic education. This study uses a type of literature research. Literature research is a research that is carried out by reviewing various journals and related reference books. The results of his research show that quality education is an essential aspect in Islam. Such quality education functions not only for the transfer of knowledge, but also for the formation of good character and morals. Quality management in Islamic education is very important, especially in building a generation of noble and quality character. The Qur'an, which is the main guide for Muslims, contains quality management principles such as focus on customer satisfaction, leadership based on the example of the Prophet, Process-based approaches, integrated managerial systems, thoughtful decision-making and mutually beneficial relationships, can all be applied in Islamic education to ensure the quality of continuous and ethical learning. With the implementation of this quality management, Islamic education is expected to create a conducive environment for learning, improve the quality of educational outcomes and produce a generation that is ready to make a positive contribution to society.